Publication Ethics As A Base For Character Education to The University Students of Indonesia - Humaidi, Humaidi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
This research aims to analyze the importance of character education for Indonesian students, especially in publication ethics as the basis for developing character education in Indonesia. Character education is needed not only for student social behaviour but also in scientific writing activities, which are an obligation for students. This research is a literature study sourced from library materials using a qualitative approach. Thus, this research activity explores several primary and secondary data with several concrete steps such as reading and studying preliminary data in research books, theses or dissertations related to character education and its relationship with publication ethics. Character education, especially in the ethical aspect of student publications, is essential as one of the basics for the development of education in Indonesia because so far, students are only oriented to the final grade, without paying attention to the meaning and spiritual values ​​behind the process itself, at least the results of the analysis in this study found four ethical values ​​in publications, namely first: Honesty, namely students in writing scientific papers must be oriented to the values ​​of honesty, and free from plagiarism, duplication, fabrication, and falsification. Second, the validity of the data (validity) is related to concepts or ideas that have an apparent legal basis reference. Moreover, the third is reliability (Reliability: accuracy and consistency). The fourth is to uphold Copyright in a scientific paper. Keyword: Publication Ethics, Character Education, University Students